PELAKSANAAN PROGRAM BANTUAN BIBIT KELAPA SAWIT DI KABUPATEN KUANTAN SINGINGI (Studi Kasus Pelaksanaan Standar Operasional Prosedur) - Penderi, Bella; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Implementation is an activity carried out by an agency or organization in a planned, organized and directed manner in order to achieve the expected goals. Therefore the Kuantan Singingi Regent issued a decree Number: Kpts.107 / V / 017 regarding technical guidelines for the distribution of oil palm seedlings in Kuantan Singingi Regency Government 2017 budget year. The purpose of this study was to determine the Implementation of Oil Palm Seed Assistance Program in Kuantan Singingi District (case study of standard operating procedures) and to find out the factors that constrained the Implementation of Oil Palm Seed Assistance Program in Kuantan Singingi District (case study of operational standard implementation procedure). The concept of the theory that the author uses is the theory of program definition by Charles O. Jones in Suryana (2009: 28) with organizing, interpretation, application or application. This study uses qualitative research methods with descriptive data review. In collecting data, the authors use interview and documentation techniques using the purposive sampling method as a source of information and use interactive models of analysis as a source of validity of the data. The results of this study indicate that the implementation of the Oil Palm Seed Assistance Program in Kuantan Singingi District (a case study of implementing standard operating procedures) is seen that the organization has not been optimal, the interpretation of the Department of Agriculture has not run effectively, and its implementation has not been able to overcome the implementation of the program. Factors that constrain the implementation of the Oil Palm Seed Assistance Program in Kuantan Singingi District (case study of standard operating procedures) are the Limitations on Human Resources and Budget Limitations. Keywords: Management, Actuating, Program Implementation in SOP